A comparative study of the feet of middle-aged women in Korea and the Maasai tribe. Issue 1 (December 2015) - Choi, Jun; Woo, Sang; Oh, Sang; Suh, Jin
Abstract Background Members of the Maasai tribe spend their days either barefoot or wearing traditional shoes made from recycled car tires. Although they walk long distances (up to 60 km) daily, they do not generally experience foot ailments. Here, we compared parameters associated with the feet, ankles, and gait of middle-aged women in Korea and the Maasai tribe. Methods Foot length, calf circumference, hindfoot alignment, step length, cadence, and walking velocity were compared among 20 middle-aged Korean and bush-living Maasai women. Static and dynamic Harris mat footprints were taken to determine the distribution of forefoot pressure patterns during walking. We also compared several radiographic parameters with standing foot and ankle radiographs. Results The mean foot length and width were significantly longer in Maasai women. Interestingly, 38 ft (96 %) in the Maasai group showed a claw deformity of the toe (s). There were no statistically significant differences in gait-related indices and Harris mat findings between the two groups. On radiographic analysis, tibial anterior surface angle, tibial lateral surface angle, talonavicular coverage angle, talo-first metatarsal angle, Meary angle, and naviculo-cuboidal overlap were significantly greater in the Maasai group, whereas hallux valgus angle and the first and second intermetatarsal angle were greater in the Korean group. Conclusions Middle-aged women from the Maasai tribe showed a higher prevalence of abducted forefeet, everted hindfeet, and fallen medial longitudinal arches than did Korean women, while Korean women showed a higher prevalence of hallux valgus, a preserved medial longitudinal arch, and toes that are free from claw deformity.